2008
DOI: 10.1021/jm801052f
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Molecular Beacon Triggered by Fibroblast Activation Protein on Cancer-Associated Fibroblasts for Diagnosis and Treatment of Epithelial Cancers

Abstract: Fibroblast activation protein (FAP) is a cell-surface serine protease highly expressed on cancer-associated fibroblasts of human epithelial carcinomas but not on normal fibroblasts, normal tissues, and cancer cells. We report herein a novel FAP-triggered photodynamic molecular beacon (FAP-PPB) comprising of a fluorescent photosensitizer and a black hole quencher 3 linked by a peptide sequence (TSGPNQEQK) specific to FAP. FAP-PPB was effectively cleaved by both human FAP and murine FAP. Using the HEK293 transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 43 publications
0
96
0
Order By: Relevance
“…Among these systems, which consist of a disease-targeted linker, a PS and a quencher, the "photodynamic molecular beacons" (PMB) developed by Zheng and co-workers are noteworthy. [51][52][53][54][55][56][57][58][59][60][61] The excited state of the PS in this aPS is efficiently quenched via Förster Resonance Energy Transfer (FRET) to a quencher that is closely positioned through a linker. When the linker is cleaved by a cancer-specific stimulus, such as an enzyme, the quencher separates from the PS associated with regeneration of its photoactivity.…”
Section: Enzymes/proteins Overexpressed In Cancer Cells Activate Specmentioning
confidence: 99%
“…Among these systems, which consist of a disease-targeted linker, a PS and a quencher, the "photodynamic molecular beacons" (PMB) developed by Zheng and co-workers are noteworthy. [51][52][53][54][55][56][57][58][59][60][61] The excited state of the PS in this aPS is efficiently quenched via Förster Resonance Energy Transfer (FRET) to a quencher that is closely positioned through a linker. When the linker is cleaved by a cancer-specific stimulus, such as an enzyme, the quencher separates from the PS associated with regeneration of its photoactivity.…”
Section: Enzymes/proteins Overexpressed In Cancer Cells Activate Specmentioning
confidence: 99%
“…Lo et al developed a novel FAP-triggered PDT beacon which could induce signi¯cant photocytotoxicity in FAP-expressing cells and be activated in FAP-expressing stromal¯broblasts in vivo. 82 Although many PS-conjugates are unsuitable for systemic administration for many reasons (e.g., systemic toxicity, high cost), they may be an ideal candidate for intratumoral delivery.…”
Section: Intratumoral Injectionmentioning
confidence: 99%
“…In vitro and in vivo experiments have validated the FAP-specific activation of FAP-PPB in cancer cells and mouse xenografts. 62 In addition, Huang et al 63 conjugated Doxorubicin (Dox) with a FAP-specific dipeptide to develop a FAP-targeting prodrug of Dox (FTPD). They demonstrated that FAP-cleaved FTPD exhibited significantly higher cytotoxicity against 4T1 cells in vitro than the uncatalyzed prodrug.…”
Section: Clinical Applications Of Fapmentioning
confidence: 99%